The Monotone and the Dominated Convergence Theorems for an Integral Involving a System of Paths - Lim, Daisy Lou; Canoy, Sergio Jr. (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Recently, Fu introduced the concept of a system of paths and used this to define an integral. For a system consisting of neighborhoods, this integral is equivalent to the Henstock integral. This paper gives the Monotone and the Dominated Convergence theorems of the E-path integral defined by Fu in (3).